Simulation to improve the flow of the hospital exam laboratory - Oliveira, Daniel Marques; Lopes, Emilli Cassia Souza; Araújo, Andressa Clara Barbosa de; Pimentel, Cristiane Agra (Brazilian Journal of Production Engineering, 2024)
Lean Healthcare is a methodology that adapts methodologies used in industry to the healthcare sector. With it, it is possible to identify bottlenecks and optimize hospital flows. Over time, however, technologies have emerged to add more and more to healthcare management, known as "Health 4.0", which, combined with Lean, achieve even more beneficial results. In reality, changing processes is risky and the chances of not achieving the expected results are enormous. The aim of this article is to demonstrate how to optimize the delivery time of laboratory tests in a health unit by studying Lean Healthcare with simulation, using an action research methodology, in a hospital in Feira de Santana, Bahia, using an analysis through a process flowchart, chrono analysis and Flexsim simulation software. The result was an analysis of the consequences of the impact of waste in the laboratory and improvements were simulated using the simulation software, reducing delivery times by up to 60%. This demonstrated the benefits of using simulation to improve the services offered in the healthcare sector.